A study of configurational alternatives of a gas-to-liquids process based on Fischer-Tropsch technology - Khazali, Ashcaan Tendo (Department of Chemical Engineering, 2022)
Environmental concerns, associated legislation, limited oil reserves and fluctuating crude oil prices are some of the factors that highlight the need for alternative and environmentally friendly routes to fuels. One alternative is to use Fischer-Tropsch Synthesis (FTS) as the major technology in conversion of carbon containing feedstock to transportation fuels. The FTS product, called syncrude, can be refined to high quality transportation fuels in Coal, Gas or Biomass to liquid plants (denoted as CTL, GTL, and BTL, respectively, and collectively referred to as XTL). The economic viability of XTL processes is generally subject to the present price of crude oil and past studies show that traditional refining is generally more economically viable. However, XTL processes have been shown to be more economical and in some cases more environmentally friendly than conventional options when legislative measures aiming to curb traditional fossil fuel usage are considered. This study explores XTL process configurations that can improve plant carbon efficiency to diesel and liquids. The configuration encompasses technologies used, operating conditions, and layout of unit operations. A basic GTL process configuration consists of an Air Separation Unit (ASU), Auto-Thermal Reforming (ATR), syngas cleaning, full conversion Low Temperature Fischer-Tropsch (LTFT) and wax hydrocracking (WHC). These operations are modeled individually and combined to produce a plant model for study with the aim of determining the effects of configurational alternatives on the process efficiency to liquids and diesel. Furthermore, given that the ASU is a major contributor to costs the effect of using oxygen-enriched or pure air is investigated. Since production of heavy wax is prioritized, FTS represents the use of cobalt catalyst in LTFT operation. Where air is used, FTS is run to high conversion in once through mode to avoid the unfavorable economics of recycling nitrogen. After separation of the syncrude, the light fraction is reformed back to syngas in order to maximize carbon efficiency. The heavy wax is hydrocracked to maximize distillate range material. The light products from the WHC are combined with the lights from FTS and the heavy wax is recycled. Carbon efficiency, liquid selectivity and diesel yield are the means of assessing performance. The Scilab programming language is used along with physical properties estimated using the COCO/ChemSep pure component database as a starting point. Estimation of properties for alkanes and olefins of carbon chain length up to C200 has been carried out. The presence of 25% nitrogen in the ATR was found to beneficial to the H2 : CO ratio in the resulting syngas. Furthermore, in FTS the presence of 10-20% nitrogen produced the lowest reduction in carbon monoxide conversion and _FTS. In general, the introduction of nitrogen resulted in decreased conversion of methane in the ATR and both decreased _FTS and conversion in FTS. WHC performance was found to benefit from alpha being as high as possible; however, when the heavy wax recycle was inactive the optimal value was 0.92. The OOT80 configuration was found to have the highest liquid selectivity, while the efficiency to diesel was maximized for the OIRC40 configuration.